2008
DOI: 10.1152/jn.01087.2007
|View full text |Cite
|
Sign up to set email alerts
|

Location of Spinal Cord Pathways That Control Hindlimb Movement Amplitude and Interlimb Coordination During Voluntary Swimming in Turtles

Abstract: Samara RF, Currie SN. Location of spinal cord pathways that control hindlimb movement amplitude and interlimb coordination during voluntary swimming in turtles. J Neurophysiol 99: 1953-1968, 2008. First published February 13, 2008 doi:10.1152/jn.01087.2007. We performed mechanical lesions of the midbody (D2-D3; second to third postcervical spinal segments) spinal cord in otherwise intact turtles to locate spinal cord pathways that 1) activate and control the amplitude of voluntary hindlimb swimming movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Examination of both extracellular and intracellular recordings in turtle fictive and nonfictive preparations by Stein, Berkowitz, Currie, Hounsgaard, and others also show both shared and dedicated neurons recruited in fictive vertebrate motor patterns (Berkowitz, 2001(Berkowitz, , 2002(Berkowitz, , 2008Alaburda et al, 2005;Stein, 2005Stein, , 2008Berg et al, 2007;Samara and Currie, 2008). However, their data cannot or did not examine modularity in terms of premotor drive, or examine EMG and force patterns as we did here.…”
Section: Spinal Interneuron Systems and Recordings In Other Lower Tetmentioning
confidence: 50%
“…Examination of both extracellular and intracellular recordings in turtle fictive and nonfictive preparations by Stein, Berkowitz, Currie, Hounsgaard, and others also show both shared and dedicated neurons recruited in fictive vertebrate motor patterns (Berkowitz, 2001(Berkowitz, , 2002(Berkowitz, , 2008Alaburda et al, 2005;Stein, 2005Stein, , 2008Berg et al, 2007;Samara and Currie, 2008). However, their data cannot or did not examine modularity in terms of premotor drive, or examine EMG and force patterns as we did here.…”
Section: Spinal Interneuron Systems and Recordings In Other Lower Tetmentioning
confidence: 50%
“…Activation of the propriospinal pathway could not be ruled out in this experiment, a possibility that has been supported in previous reports [12]. Studies have emphasized the integrative function of the propriospinal pathways between upper and lower limbs [13]. However, as mentioned above either tracts carrying these signals is a speculative venture.…”
Section: Upper Middle and Lower Cervical Stimulation Evoked Muscular Signals In Lower Limb Muscles Action Potentials Amplitude And Potentsupporting
confidence: 49%
“…There are a number of neural mechanisms available to ensure appropriate coordination of the legs and arms during balance reactions. Based on the results of studies in the cat (Gernandt and Megirian 1961;others 1973, 1975;Skinner and others 1980) and, more recently, in the turtle (Samara and Currie 2008) and neonatal rat (Juvin and others 2005), it has been suggested that propriospinal pathways provide the necessary link between the lumbrosacral and cervical spinal segments responsible for controlling the lower and upper limbs, respectively. In humans, interlimb reflexes have been identified whereby electrical stimulation of the foot (Kearney and Chan 1979) or mechanical perturbation of the ankle (Kearney and Chan 1981) produces responses in the muscles of the arms.…”
Section: Neural Mechanisms Of Upper and Lower Body Coordinationmentioning
confidence: 99%